2014
DOI: 10.1002/2014gl061884
|View full text |Cite
|
Sign up to set email alerts
|

Hot upwelling conduit beneath the Atlas Mountains, Morocco

Abstract: The Atlas Mountains of Morocco display high topography, no deep crustal root, and regions of localized Cenozoic alkaline volcanism. Previous seismic imaging and geophysical studies have implied a hot mantle upwelling as the source of the volcanism and high elevation. However, the existence, shape, and physical properties of an associated mantle anomaly are debated. Here we use seismic waveform analysis from a broadband deployment and geodynamic modeling to define the physical properties and morphology of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 47 publications
3
35
0
Order By: Relevance
“…Our findings are consistent with values derived from modeling of hotspots tracks beneath the continental lithosphere (~300 °C, Yang & Leng, ). In addition, results from seismic waveform analysis combined with geodynamic modeling reveal a strong T excess of ~350 ± 90 °C in this region (for dry mantle), which is inferred to be solely of thermal origin, although a small quantity of partial melt and volatiles may be present (Sun et al, ). d T S estimates appear to be slightly higher than d T P in the innermost parts of the low‐velocity anomaly (see Figures e and k).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with values derived from modeling of hotspots tracks beneath the continental lithosphere (~300 °C, Yang & Leng, ). In addition, results from seismic waveform analysis combined with geodynamic modeling reveal a strong T excess of ~350 ± 90 °C in this region (for dry mantle), which is inferred to be solely of thermal origin, although a small quantity of partial melt and volatiles may be present (Sun et al, ). d T S estimates appear to be slightly higher than d T P in the innermost parts of the low‐velocity anomaly (see Figures e and k).…”
Section: Discussionmentioning
confidence: 99%
“…We compare our temperature model with those of previous studies in the region from thermobarometry calculations (Thurner et al, ), receiver functions (Morais et al, ), waveform analysis (Sun et al, ), and geophysical‐petrological modeling (Fullea et al, and personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested a thin lithosphere beneath the High and Middle Atlas to support its elevation and to explain the strong positive geoid anomaly [Teixell et al, 2003Ayarza et al, 2005;Zeyen et al, 2005;Fullea et al, 2010]. Different processes have been proposed to explain the source of the shallow asthenosphere: (1) a mantle plume that is part of the Canary system Missenard et al, 2006;Duggen et al, 2009;Miller and Becker, 2013;Sun et al, 2014;Miller et al, 2015], (2) lateral flow of asthenospheric mantle at the edge of the Alboran slab , (3) flow caused by edge-driven convection [Missenard and Cadoux, 2012;Kaislaniemi and van Hunen, 2014], and (4) delamination of the local upper mantle beneath the High and Middle Atlas [Bezada et al, 2014]. All these processes result in a Geochemistry, Geophysics, Geosystems 10.1002/2016GC006657 thinner lithosphere.…”
Section: Alboran and Atlas Regionmentioning
confidence: 99%
“…Many recent efforts have focused on understanding the crustal‐ and lithospheric‐scale structure of the Atlas to understand the orogenesis. Structural seismological imaging suggests that the lithosphere beneath the Atlas is particularly thin or perhaps the uppermost mantle is abnormally warm with low seismic velocities found at depths of ~65–160 km (e.g., Bezada et al, ; Fullea et al, ; Miller et al, ; Palomeras et al, ; Sun et al, ). Figure shows S receiver function estimates of the Moho and lithosphere‐asthenosphere depths along a profile across the Atlas from Miller and Becker ().…”
Section: The Atlas Orogenmentioning
confidence: 99%